Design of an OPAMP-RC lowpass filter in 22 NM FDSOI technology - Keleş, Ömer Taha (Graduate School, 2022)
Analog filters are widely used in signal processing applications like noise reduction, blocker rejection, signal detection, anti-aliasing, demodulation, audio processing etc. They are utilized to allow certain signals to pass while blocking others. Passed or blocked signals are not time dependent since analog filters are time invariant circuits. These filters pass or block signals depending on the signal's frequency, meaning that signals in specified frequency ranges are blocked or passed. While time domain responses of the filters are still a critical design consideration, filters are mainly designed considering the desired frequency domain responses. Main types of filters can be categorized as lowpass, highpass, bandpass and bandstop according to their selective frequency range. There are various types of lowpass filter responses which have different passband or stopband characteristics. Brick wall response, whose pass and stop bands are separated at the corner frequency, has a discontinuous frequency response. This type of a mathematical function is not realizable in real world. On the other hand, realizable filter responses are continuous functions with finite roll-off slopes between stopband and passband. The slope at the transition band depends on the order of the filter function and the type of the filter function. Additionally in real filter functions there may be permitted fluctuations which may appear in stopband, passband or both. In Butterworth response, the passband has flat frequency characteristics so it is called maximally flat magnitude response. Likewise, Chebyshev type I filter response has equal ripples in the passband so it is called equal ripple magnitude response. Chebyshev type II filter response, or equal ripple stopband magnitude response, has equal ripples in the stopband and Cauer filters have ripples in both stopband and passband. The question of how to realize filter functions with real circuit elements arises numerous solutions. Such filter functions can be realized using circuit elements like resistors, capacitors, inductors and some specialized circuit elements such as operational amplifiers and switched capacitors. Filter characteristics and design limitations vary greatly depending on the circuit elements and topologies used. In order to realize lowpass filter functions, various different circuit topologies are proposed over the last couple of decades. Filters are classified depending on the circuit elements employed. LC ladder filters consist of inductors, capacitors and resistors which are all passive elements. Besides resistors and capacitors, Opamp-RC filters utilize active circuit elements called operational amplifiers. Moreover, OTA-C filters are implemented using operational transconductance amplifiers and capacitors. Furthermore, capacitors, operational amplifiers and switched capacitor circuits are used to build switched capacitor filters. All the different circuit topologies have their advantages and disadvantages. It is the designer's job to determine which topology is a better choice considering the design specifications and limitations. Over the years, shrinking of transistor sizes resulted in reduced analog performance and lower voltage headroom.
22 NM FDSOI teknolojisinde OPAMP-RC alçak geçiren filtre tasarımı
Thesis (M.Sc.) -- İstanbul Technical University, Graduate School, 2022
Keywords: integrated circuits; active filters; integrated circuits design; operational transconductance amplifier; filter circuits